Basic statistics using Excel 2007 : for Statistical techniques in business & economics - Lin, Douglas A., author; Merchant, Ronald; Marshall, William G.; Wathen, Samuel Adam. (New York : McGraw-Hill Irwin, 2012)
Thompson, Strickland and Gambles, CRAFTING AND EXECUTING STRATEGY, 17/e presents the latest research findings from the literature and cutting-edge strategic practices of companies have been incorporated to keep step with both theory and practice. The chapter content continues to be solidly mainstream and balanced, mirroring both the best academic thinking and the pragmatism of real-world strategic management.
Includes bibliographical references.
In English text.
Keywords: Microsoft Excel (Computer file) -- Problems, exercises, etc; Statistics -- Problems, exercises, etc; Microsoft Excel (Computer file).; Statistics